Patient and Provider Attitudes and Preferences Regarding Early Palliative Care Delivery for Patients with Advanced Gastrointestinal Cancers: A Prospective Survey - Oren Levine; Daryl Bainbridge; Gregory R. Pond; Marissa Slaven; Sukhbinder Dhesy-Thind; Jonathan Sussman; Ralph M. Meyer (Current Oncology, 2024)
Early integrated palliative care (EIPC) for patients with advanced cancers requires the involvement of family doctors (FDs) and oncologists. We compared attitudes between patients and their providers regarding the delivery of EIPC. Patients with newly diagnosed incurable gastrointestinal (GI) cancer at a tertiary cancer centre in Ontario, Canada, were surveyed using a study-specific instrument regarding the importance of and preferences for accessing support across eight domains of palliative care. Physicians within the circle of care completed a parallel survey for each patient. The concordance between patient and physician responses was analyzed. A total of 66 patients were surveyed (median age 69, 35% female). All had an oncologist, 12% had a specialist palliative care provider (SPC), and 97% had an FD, but only 41% listed the FD as part of the care team. In total, 95 providers responded (oncologist = 68, FD = 21, SPC = 6; response rate 92%; 1–3 physician responses per patient). Disease management and physical concerns were most important to patients. Patients preferred to access care in these domains from oncologists or SPCs. For all other domains, most patients attributed primary responsibility to self or family rather than any healthcare provider. Thus, concordance was poor between patient and physician responses. Across most domains of palliative care, we found low agreement between cancer patients and their physicians regarding responsibilities for care, with FDs appearing to have limited involvement at this stage.